Open Patent Ductus Arteriosus (PDA) in a 20-Year Old Killer Whale (Orcinus Orca): A Pathological Study. - Rodríguez Lorenzo, Gabriela (2023)
The complex events evolved in the embryologic development of the heart and great vessels in humans and animals allow substantial opportunities for congenital anomalies to develop (Zachary, 2022). Congenital heart anomalies have been reported in different species of terrestrial mammals but not as frequent in marine mammals. In these, most of the references are related to pinnipeds but only it has been very rare described in cetaceans, either in wildlife or in captivity (under human care) (Dennison, Boor, et al., 2011). In the very few cetaceans in which congenital heart defects have been reported, those were diagnosed during the necropsy in animals that died days or few weeks after birth. In the scientific literature, congenital cardiac defects have not been reported in juvenile or adult cetaceans (Gulland et al., 2018). This work shows the diagnosis of a Persistent Ductus Arteriosus (PDA) in a 20-year-old female Killer Whale (Orcinus orca). A complete pathological case study of Kohana (name of this killer whale) was carried. Necropsy and histology showed that this Killer Whale suffered a cardiovascular anomaly from birth classified as congenital/development heart defect. She showed a large and open patent ductus arteriosus (PDA) associated with lesions consistent with a severe chronic pulmonary hypertension connected with chronic heart lesions affecting systemically to other organs which ultimately led to heart failure and death. It is reported, up to our best knowledge, for the first time, an open Persistent Ductus Arteriosus (PDA) and the associated chronic systemic pathology, in a 20-year-old Killer Whale (Orcinus orca) which was born in captivity.